The concept of inter - firm partnering practice between client and contractor in the construction projects / Faridah Muhamad Halil, Mohamad suffian Hasim and Siti Mazuen Kamaruddin - Muhamad Halil, Faridah; Hasim, Mohamad suffian; Kamaruddin, Siti Mazuen (Universiti Teknologi MARA, 2021)
Interfirm collaboration is a cooperation between business organisations that allow achieving their common goals more effectively. Through partnering concept of collaboration, the organisation will gain the benefits in terms of the project successfully run according to the time, cost and quality. The understanding of this concept of Partnering is crucial for the clients in the construction project, without this knowledge of partnering concept the client will suffer cost overruns, delay, more variation order and dispute in the project implementation. The study conducted using a quantitative approach and involved the sampling from public and private clients. The main result indicates that that the public clients and private client understood the concept of Partnering. Public clients agreed that specific projects require partnering with contractors. Suitability of the projects is complex projects, critical project and long term development. High impact projects in the public clients are given to the contractors that shows the capabilities and good reputation from the previously completed project. However, Private clients stated that projects that are critical to the client's business are suitable for the partnering concept.